Enhancing Early Childhood Social-Emotional Skills through Gardening Activities in Group A at Pelita Harapan Kindergarten - Sofia Jamiatul Rohmah (DAAR EL-KAMIL: Multidisciplinary Journal, 2026)
This research is motivated by the low social-emotional abilities of children in Group A at TK Pelita Harapan, as indicated by difficulties in sharing, cooperating, and managing emotions appropriately. The purpose of this study is to improve children's social-emotional abilities through gardening activities. The method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model implemented in two cycles. The research subjects were 15 children in Group A at TK Pelita Harapan. Data collection techniques included observation, documentation, and field notes. The results showed a significant improvement in children's social-emotional abilities. In the initial condition (pre-cycle), children's social-emotional abilities only reached 33.33% in the Developing as Expected (BSH) category. In Cycle I, it increased to 60.00%, and in Cycle II, it increased to 86.67%. Gardening activities have been proven to develop aspects of patience, responsibility, cooperation, empathy, and self-control through meaningful direct experiences. Thus, gardening activities can serve as an effective alternative learning method to improve social-emotional abilities in early childhood.